Dysphagia Secondary to Anterior Cervical Fusion: Radiologic Evaluation and Findings in 74 Patients - Carucci, Laura R.; Turner, Mary Ann; Yeatman, C. Fitzhugh (American journal of roentgenology (1976), 2015)
The objective of our study was to assess the frequency, cause, and time course of dysphagia after anterior cervical fusion (ACF). A review of the surgical database revealed that 1789 patients underwent ACF procedures during the 8-year study period. A radiologic database review indicated that 80 of the 1789 patients underwent radiologic evaluation for the assessment of dysphagia after ACF. Three patients were excluded from the study because they had a history of dysphagia before ACF, and three additional patients were excluded because they had more recently undergone Nissen fundoplication, intubation, and radiation therapy, respectively. Modified barium swallow (MBS) studies and esophagrams of the 74 remaining patients were collected and analyzed to determine the cause of dysphagia and time course of dysphagia onset after surgery. Dysphagia was evaluated radiologically in 74 of the 1789 ACF patients (4.1%) using video MBS studies (n=66) and esophagography (n=26). Patients underwent radiologic evaluation from 1 to 1150 days after surgery (mean, 120 days after surgery); 76% of the patients presented more than 2 weeks after surgery. The location of the ACF in the study group was the upper, mid, and lower cervical spine in 5.4% (n=4), 55.4% (n=41), and 39.2% (n=29) of patients, respectively. Soft-tissue swelling with displacement of the pharynx or esophagus was identified in 91% of patients (n=67). More serious complications of ACF that resulted in dysphagia included surgical hardware displacement or bone graft displacement (n=18), esophageal perforation (n=3), and a retropharyngeal abscess (n=3). Pharyngeal functional abnormalities were detected in 50 patients, with penetration, aspiration, or both seen in 32. Dysphagia is an underrecognized but significant complication of ACF. After ACF, 4.1% of patients presented for radiologic evaluation of dysphagia. Although ACF procedures are most frequently performed in the lower cervical spine, dysphagia is a more common clinical problem after ACF in the mid cervical spine. Radiologic examinations should be specifically tailored to evaluate ACF patients.